Perancangan Model Hirarki Keputusan dan Sistem Basis Data pada Sistem Informasi Sumber Daya Manusia Sub-Sistem Rekrutmen dengan Metode Berjenjang - Miranda, Eka; Julisar, Julisar (Bina Nusantara University, 2013)
Management of employees as a resource is essential to enhance the effectiveness of employee’s performance, and the process efficiency of for organizations or companies. Possible problems related to the management of human resources need to be diagnosed which one to be solved as a priority. The problem is how to design the decision making model to help the Human Resource Department in determining the criteria for recruitment which can be used to take decisions on recruitment of human resources. This research aims to design a model of decision making systems and databases to support accuracy of decision making in human resource information system to create high loyalty and productivity so that the productivity of the company can be further improved. The research is divided into two phases: collection as well as analysis of data and design model. Specifically target to be achieved in this research are to identify the critical success factors of the model of decision making system for recruitment and develop models of decision-making system. The results obtained from this research are hierarchical decision models using analytical hierarchy process and its database design for the recruitment sub-system of human resource.